Composition and Abundance of NaGISA-Sampled Seagrass Meiofauna in Taklong Island National Marine Reserve (TINMAR) for 2012-2013 - Sorolla, Doreen Joy (2015.)
Meiofaunal assemblages reflect the general health of marine benthos of an area. Initial survey of meiofauna in Calaparan seagrass beds in Taklong Island National Marine Reserve (TINMAR) began in 2005 as part of the global monitoring of near shore biodiversity under the NaGISA program. During the course of annual monitoring, the area was subjected to anthropogenic (oil spill in 2006) and natural (typhoon in 2008) disturbances. Their effects reflected on the decline and loss of meiofauna. This study aimed to examine the community structure of meiofauna in Calaparan seagrass site in TINMAR for 2012 and 2013. Two transects were laid parallel to the shore: one in intertidal zone and another in subtidal zone at 1 m depth. The sampling followed the NaGISA protocol for soft bottom seagrass sites. Nematodes (39%), harpacticoids (32%), and polychaetes (9%) were the major taxa comprising the meiofauna in the area. Syllids, capitellids, nereids, and sabellids were the most abundant polychaete families. T-tests were used to determine differences between years and transects. There was no siginificant temporal and spatial difference in meiofaunal composition and abundance, although there was a consistent higher diversity in the subtidal than the intertidal. Percentage of seagrasses cover was also higher in subtidal zone. Sediment composition in both transects in both years are largely composed of coarse sand and granules.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Taklon Island National Marine Reserve (TINMAR); Seagrass -- Calaparan; Taklong Island